Pengaruh Polimorfisme Gen terhadap Risiko Penyakit Gagal Ginjal Kronis: Narrative Review - Handani, Dewa Ayu Sri; Megawati, Fitria (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Chronic Kidney Disease (CKD) is an escalating global health issue, particularly in Indonesia. CKD is characterized by a progressive and irreversible decline in renal function, with diabetes mellitus and hypertension as primary risk factors. Genetic polymorphisms, variations in DNA sequences that affect gene function and protein expression, play a critical role in CKD risk and progression. This narrative review examines the role of genetic polymorphisms in CKD risk based on available literature. Scientific articles were sourced from PubMed, ScienceDirect, Google Scholar, and Scopus using keywords related to genetic polymorphisms and CKD. From the 441 articles identified, selection was based on relevance, sample size, and article completeness. Several genetic polymorphisms were found to have significant associations with increased CKD risk, including Renalase (rs2296545), GSTO1 (rs2164624), GSTO2, MMP3 (rs35068180), and MGP (rs4236), among others such as CYP24A1, GPX1, UMOD, CYP2C8, CYP4A11, EPHX2, SPP1, and BGLAP. These polymorphisms influence mechanisms such as blood pressure regulation, oxidative stress, inflammation, and tissue calcification, all contributing to CKD progression. In conclusion, genetic polymorphisms are crucial in CKD risk, offering insights for more personalized approaches in diagnosing, preventing, and treating this condition. These findings support the development of more effective, genetics-based treatment strategies in the future.